Association of rs10204525 genotype GG and rs2227982 CC combination in programmed cell death 1 with hepatitis B virus infection risk. Issue 35 (August 2019) - Huang, Chunhong; Ge, Tiantian; Xia, Caixia; Zhu, Wei; Xu, Lichen; Wang, Yunyun; Wu, Fengtian; Liu, Feifei; Zheng, Min; Chen, Zhi
Abstract : Abstract: Single nuclear polymorphism (SNP) of programmed cell death 1 (PD-1) was reported associated with hepatitis B virus (HBV) infection, but the SNP sites studied were limited. Whether the combination of 2 or more SNP sites could better represent the relationship between PD-1 SNP and HBV infection was not studied. Eight hundred ninety-eight HBV-infected patients (222 asymptomatic carriers [AsC], 276 chronic hepatitis B, 105 acute-on-chronic liver failure, and 295 liver cirrhosis) and 364 health controls of South China were enrolled in this study. Four PD-1 SNPs (rs10204525, rs2227982, rs41386349, and rs36084323) were selected and detected by TaqMan probe. The frequency of allele, genotype, and combination of different SNPs were compared between different groups. For allele frequency analysis, G allele of rs10204525 was protective factor (odds ratio (OR) = 0.823, 95% confidence interval (CI) = 0.679–0.997, P  = .046) and T allele of rs2227982 was predisposing factor (OR = 1.231, 95% CI = 1.036–1.463, P  = .018) in HBV infection. When analyzed in genotype frequency, the genotype GG of rs10204525 and CC of rs2227982 were protective factor of HBV infection. Combination of rs10204525 GG and rs2227982 CC was potent protective factor of HBV infection (OR = 0.552, 95% CI = 0.356–0.857, P  = .007) and was also associated with lower HBV load (OR = 0.201, 95% CI = 0.056–0.728, P  = .008) in AsC. The 4 SNP sites were not associated with progression of HBV-related liver disease. Rs10204525 and rs2227982 of PD-1 associate with HBV infection and combination of the 2 SNP sites can better predict host susceptibility in HBV infection. Abstract : Supplemental Digital Content is available in the text